The Role of Properdin in Killing of Non-Pathogenic Leptospira biflexa - Martinez, Adriana Patricia Granados; Abreu, Patrícia Antonia Estima; de Arruda Vasconcellos, Silvio; Ho, Paulo Lee; Ferreira, Viviana P.; Saggu, Gurpanna; Barbosa, Angela Silva; Isaac, Lourdes (Frontiers in Immunology, 2020)
Properdin (P) is a positive regulatory protein that stabilizes the C3 convertase and C5 convertase of the complement alternative pathway (AP). Several studies have suggested that properdin can bind directly to the surface of certain pathogens regardless of the presence of C3bBb. Saprophytic Leptospira are susceptible to complement-mediated killing, but the interaction of properdin with Leptospira spp. has not been evaluated so far. In this work, we demonstrate that properdin present in normal human serum, purified properdin, as well as properdin oligomers P2, P3, and P4, interact with Leptospira. Properdin can bind directly to the bacterial surface even in the absence of C3b. In line with our previous findings, AP activation was shown to be important for killing non-pathogenic L. biflexa, and properdin plays a key role in this process since this microorganism survives in P-depleted human serum and the addition of purified properdin to P-depleted human serum decreases the number of viable leptospires. A panel of pathogenic L. interrogans recombinant proteins was used to identify putative properdin targets. Lsa30, an outer membrane protein from L. interrogans, binds to unfractionated properdin and to a lesser extent to P2-P4 properdin oligomers. In conclusion, properdin plays an important role in limiting bacterial proliferation of non-pathogenic Leptospira species. Once bound to the leptospiral surface, this positive complement regulatory protein of the AP contributes to the formation of the C3 convertase on the leptospire surface even in the absence of prior addition of C3b.